2020
DOI: 10.1111/jace.17269
|View full text |Cite
|
Sign up to set email alerts
|

Model for the cold sintering of lead zirconate titanate ceramic composites

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Wang et al 31 studied cold sintering of PZT ceramics with lead nitrate as a sintering aid. In the initial stages of pressing, particle rearrangement led to rapid densification.…”
Section: Dielectric Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang et al 31 studied cold sintering of PZT ceramics with lead nitrate as a sintering aid. In the initial stages of pressing, particle rearrangement led to rapid densification.…”
Section: Dielectric Measurementsmentioning
confidence: 99%
“…Using PbAc trihydrate as a PZT sintering aid, it was found that the pressure dependence of the densification can be described either with the viscous phase sintering model 31,41 or the liquid phase sintering model as seen in Figure 4A. 42,43 Therefore, the pressure dependence of the relative density alone cannot be used to determine the densification mechanism.…”
Section: Dielectric Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the mainstream in the CSP scientific community 6 is that the process is fundamentally based on liquid phase sintering (LPS), originating from dissolution/reprecipitation phenomena, recent experimental and theoretical works seem to suggest that additional mechanisms could be relevant such as water-induced plastic or viscous flow. [11][12][13][14][15] The first materials produced by CSP were mainly salts and soluble compounds, 3,16 although several activities have been then carried out on ferroelectrics, [16][17][18] piezoelectrics, 19 magnetic ceramics, 20 semiconductors, [21][22][23] transparent ceramics, 24 bioceramics, 14 and ionic conductors. [25][26][27] More recent works regard water-assisted cold processing of silicate ceramics including cold sintering of quartz, 28 soda-lime silicate glass, 15 and quartz-PTFE composite 29 or cold joining of silica 30 and cold isotactic pressing of glass monoliths.…”
Section: Introductionmentioning
confidence: 99%
“…The process is carried out at near RT and the die/punches assembling is not sealed thus allowing water evaporation. Despite the mainstream in the CSP scientific community 6 is that the process is fundamentally based on liquid phase sintering (LPS), originating from dissolution/reprecipitation phenomena, recent experimental and theoretical works seem to suggest that additional mechanisms could be relevant such as water‐induced plastic or viscous flow 11–15 …”
Section: Introductionmentioning
confidence: 99%